2007
DOI: 10.1063/1.2737127
|View full text |Cite
|
Sign up to set email alerts
|

Defect-induced electrical conductivity increase in individual multiwalled carbon nanotubes

Abstract: The authors demonstrate that ozone exposure of individual multiwalled carbon nanotubes (CNTs) results in up to threefold increase in CNT conductivity and 50% decrease in carrier transport activation energy. Ozone exposure induces bond breaking in the individual shells and promotes cross-shell bridging via sp3 bond formation. Intershell bridging facilitates charge carrier hopping to inner shells, which can serve as additional charge carrier transport pathways, offsetting the effect of defect-scattering-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…CNTs with defects, which were generally regarded to have mechanical, 14 electrical, 15 and thermal disadvantages, 16 were shown to exhibit intriguing properties for many emerging applications such as nano-sensors, 17 super conductors, 18 catalysts, 19 and field effect transistors. 20 In this study, the hydrophobic-hydrophilic composite interfaces were synthesized by partially oxidizing pristine MWCNT surfaces to form hydrophilic carboxylic and hydroxylic functional groups on the defect sites of MWCNTs.…”
mentioning
confidence: 99%
“…CNTs with defects, which were generally regarded to have mechanical, 14 electrical, 15 and thermal disadvantages, 16 were shown to exhibit intriguing properties for many emerging applications such as nano-sensors, 17 super conductors, 18 catalysts, 19 and field effect transistors. 20 In this study, the hydrophobic-hydrophilic composite interfaces were synthesized by partially oxidizing pristine MWCNT surfaces to form hydrophilic carboxylic and hydroxylic functional groups on the defect sites of MWCNTs.…”
mentioning
confidence: 99%
“…A large defect density increases scattering events and therefore the probability of scattering into a neighboring shell. It was also shown that broken bonds can rearrange with other shells increasing the intershell conductivity [31]. Consequently, it is not completely surprising that the non-local potential is increased compared to samples A-C, indicating a larger amount of current flowing in the inner shells ( fig.…”
Section: Chapter 5 Results Obtained At Room Temperaturementioning
confidence: 96%
“…Intershell connections can also be induced artificially by breaking bonds via ozone exposure. The atoms rearrange creating sp 3 orbitals and cross-link the shells [31]. This may lead to a increased transmission probability between the shells.…”
Section: The Reality: Dirt and Defectsmentioning
confidence: 99%
“…2 In such networks, however, unexpected distortions of CNTs at basic subassemblies such as contacts and branches occasionally occur during fabrication. The local distortions modulate the electronic states of CNTs, [3][4][5] resulting in the discontinuity or degradation of electron transport. Knowledge about the origin and cause of electronic modulation in CNT networks is crucial to realize integrated circuits; however, undesirable electronic modulations cannot be easily detected in the images of CNTs obtained by simple microscopic techniques.…”
Section: Introductionmentioning
confidence: 99%